(untitled) (Journal of actual problems of jurisprudence, 2026)
The article provides a comprehensive analysis of the legal foundations and mechanisms for protecting the labor rights of hired workers within the framework of administrative law and administrative justice in the Republic of Kazakhstan. The study examines the powers and interactions of authorized state bodies that play a key role in the regulation and protection of labor relations — the State Labor Inspectorate, the Prosecutor’s Office, and the Commissioner for Human Rights. Particular attention is given to the potential of the administrative justice system under the Administrative Procedure and Process Code of the Republic of Kazakhstan (APPC) in influencing labor relations and in contesting acts, actions (or inactions) of state bodies as an effective legal remedy. This analysis helps to identify the role of administrative justice in ensuring the protection of labor rights, as well as to develop institutional and regulatory recommendations for improving law enforcement practice. The purpose of the article is to conduct a comprehensive study of administrative justice as a legal tool for protecting the rights of hired workers. The study identifies the role of administrative proceedings and other mechanisms of administrative justice (pre-trial appeals, prosecutorial supervision, and other institutions) in ensuring the protection of labor rights. Special attention is paid to international labor standards, particularly the conventions of the International Labour Organization (ILO), the decisions of the European Court of Human Rights, and the regulatory acts of the European Union. Based on the experiences of Germany and France, the article analyzes effective models of protecting labor rights through administrative procedures. A comparative analysis of national and foreign practices revealed legal gaps and institutional difficulties that arise in the implementation of the administrative justice system. In this regard, measures are proposed to improve national legislation, clarify the jurisdiction of administrative courts, and enhance the effectiveness of administrative procedures in protecting labor rights. Keywords: administrative justice, labor disputes, labor inspectorate, administrative procedures, public-law disputes, administrative act, civil servant.